The language of graphic design an illustrated handbook for understanding fundamental design principles - Poulin, Richard; ProQuest (Firm) (Beverly, Mass. : Rockport Publishers, 2011)
'The Language of Graphic Design' provides graphic design students and practitioners with an in-depth understanding of the fundamental elements and principles of their language, what they are, why they are important and how to use them effectively.
Point -- Line -- Shape -- Form -- Light -- Color -- Texture -- Scale -- Movement -- Space -- Balance -- Symmetry -- Asymmetry -- Tension -- Closure -- Expression -- Abstraction -- Tone -- Contrast -- Figure ground -- Frame -- Proportion -- Image -- Pattern -- Typography -- Grid.
BIBINDX
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Graphic arts; Design; Electronic books